VD_FINDINFO HC / 2015 / 278 vom 16. Februar 2015 - VD Tribunal cantonal (2015)
ASSISTANCE JUDICIAIRE, INDEMNITÉEN GÉNÉRAL, RÉDUCTIONEN GÉNÉRAL | 110 CPC (CH), 122 CPC (CH), 320 CPC (CH), 322 al. 1 CPC (CH), 2 al. 1 RAJ